Theories of Endogenous Regional Growth Lessons for Regional Policies - Johansson, Börje; Karlsson, Charlie; Stough, Roger R. (Springer Berlin Heidelberg, 2001)
During the last two decades a new growth theory has emerged - often labelled "endogenous economic growth". The contributions in the book develop these advances into a theoretical framework for endogenous regional economic growth and explain the implications for regional economic policies in the perspective of the new century. Endogenous growth models can reflect increasing returns and hence refer more adequately to empirical observations than earlier models, and the models become policy relevant, because in endogenous growth models policy matters. Such policies comprise efforts to stimulate the growth of knowledge intensity of the labour supply and knowledge production in the form of R&D.
Keywords: Regional/Spatial Science; Geography, general; Landscape/Regional and Urban Planning; Social Sciences, general; Regional economics; Spatial economics; Geography; Regional planning; Urban planning; Social sciences; Wachstumstheorie; Regionalentwicklung; Regionalpolitik; Endogenes Potenzial; Endogenes Wirtschaftswachstum; Konferenzschrift; Aufsatzsammlung